Onco-Esthetics Dilemma: Is There a Role for Electrocosmetic-Medical Devices? - Palmieri, Beniamino; Palmieri, Lucia; Mambrini, Andrea; Pepe, Valentina; Vadalà, Maria (Frontiers in Oncology, 2021)
OBJECTIVE: The primary aim of this review is to verify whether the warning against the use of electromedical instruments in the cosmetic professional or medical cancer patients settings is consistent with evident oncological risks supported by, experimental in vitro/in vivo studies, or anecdotal clinical reports, or any other reasonable statement. METHODS: MEDLINE, PubMed, Embase, AMED, Ovid, Cochrane Controlled Trials Register and Google Scholar databases were electronically searched. Data relating to research design, sample population, type of electro-cosmetic devices used, were extracted. RESULTS: The search strategy identified 50 studies, 30 of which were potentially relevant. CONCLUSIONS: Our research is in favor of moderate periodical use of cosmetic medical devices in patients bearing tumors, any stage like in healthy people. Special consideration is dedicated to massage, manipulation and pressure delivery upon the cytoskeleton of cancer cells that has proven to be sensitive to mechanical stress at least in some specific locally relapsing cancers such as osteosarcoma.